Predictive factors for the sensitivity of radiotherapy and prognosis of esophageal squamous cell carcinoma. (May 2014) - Wu, Shaobin; Wang, Xianwei; Chen, Jin-Xiang; Chen, Yuxiang
Abstract Purpose: To identify predictive biomarkers for radiosensitization and prognosis of esophageal squamous cell carcinoma (ESCC). Materials and methods: A total of 150 advanced stage ESCC patients were treated with preoperative radiotherapy. The protein levels of Dicer 1, DNA methyltransferase 1 (Dnmt1), and DNA-dependent protein kinase catalytic subunit (DNA-PKcs) and the mRNA levels of Dicer 1, Dnmt1, and let-7b microRNA (miRNA) were measured in ESCC tumor tissues before and after radiotherapy. Global DNA methylation was measured and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining was performed. Results: Negative Dicer 1, Dnmt1, and DNA-PKcs protein expression were observed in 72%, 67.3%, and 50.7% of ESCC patients, respectively. Primary Dicer 1 and Dnmt1 expression positively correlated with radiation sensitization and longer survival of ESCC patients, while increased Dicer 1 and Dnmt1 expression after radiation correlated with increased apoptosis in residual tumor tissues. Dicer 1 and Dnmt1 expression correlated with let-7b miRNA expression and global DNA methylation levels, respectively. In contrast, positive DNA-PKcs expression negatively correlated with radiation-induced pathological reactions, and increased DNA-PKcs expression correlated with increased apoptosis after radiation. Conclusion: Global DNA hypomethylation and low miRNA expression are involved in the sensitization of ESCC to radiotherapy and prognosis of patients with ESCC.